Emerging Challenges in Early Childhood Education: A Psycho-social Perspective - Choudhary, Dr Krishna Chandra (THE PRIMARY TEACHER, 2012)
The importance of the first six years of a child’s life is globally recognised to be the most critical years for life-long development since pace of development in these years is extremely rapid. Studies in neuro sciences have provided convincing evidence of critical periods located within these early years for forming of synaptic connections in brain and for the full development of its potential. Researches have also indicated that if these early years are not supported by, or embedded in, a stimulating and enriching physical and psychological environment, the chances of child’s brain developing to its full potential are considerably and often irreversibly reduced. This is also important as a foundation for inculcation of socio-cultural and personal values in children. It is well established that the period of early childhood years lays strong foundation for personality development.